Gestion des ecosystemes forestiers denses d'Afrique tropicale humide: 1. Gabon - Dupuy, B.; Gerard, C.; Maitre, H.F.; Marti, A.; Nasi, Robert (Centre de Coopération Internationale en Recherche Agronomique pour le Développement, 1998)
This publication compiles and synthesises information on forest ecosystems with a view to transferring this knowledge to professionals and institutions involved in research and training. The chosen references provide an up-to-date picture of achievements in sustainable management of forest resources in Gabon. There is particular concern in this region of French-speaking Africa about problems linked to sustainable management of forest resources. Programmes dealing with the sustainable management of tropical forests must take into account environment, (soils, climate as well as biodiversity), economics, sociology, interaction with wild fauna, etc. The vegetation and flora of this area, ecology, environmental problems, and pilot management programmes have given rise to an array of research aimed at better knowledge and rational utilisation of the potential of forest resources. This research includes such aspects as transport of timber, non-timber forest products and the wild fauna. This review of the literature does not aim to be exhaustive, especially in the field of silviculture and forest management. This mass of information provides a base for further work, and brings to the attention of all actors work published in specialised journals, proceedings of international fora and selected reports in grey literature. The chosen references include real experiences or reflections directly derived from the field and mission reports describing the situation over a limited period in a particular geographical area. Other documents deal with field research carried out by students, consulting firms, research centres, financing institutions, and are in the form of unpublished papers, reports of activity, synthesis, etc. For example, documents prepared by the Gabon component of ECOPAC Project are included in the review.